(untitled) (Світ фінансів, 2017)
Луців Б. Л. Кредитно-інвестиційна діяльність банків України. Розглянутометодологічні засади формування кредитної політики банку. Вказано на специфіку проблем банківського інвестиційного кредитування. Основну увагу зосереджено на аналізі поточного стану підприємства-позичальника. Lutdiv B. Credit and Investment Activity of the Ukrainian Banks. In the article the methodological backgrounds of the forming of bank’s credit policy are considered. The specific of problems of banking investing credit process are described. The main attention concentrated on analyze of modern positions of enterprises debtor.